IDENTIFIKASI FAKTOR MATERNAL YANG BERKONTRIBUSI TERHADAP KEJADIAN BERAT BADAN LAHIR RENDAH - Aryatika, Karera; Umar, Hermita Bus; Mariani, Andi; Amin, Hadriyani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Infants born weighing below this threshold have a much higher risk of mortality compared to infants born at normal weight. The aim of the study was to identify maternal factors that contribute to the incidence of low birth weight. The research design used in this study was cross sectional. The research was conducted at Sari Asih Hospital. The study was conducted in August 2024. The population is babies who experience LBW in Sari Asih Hospital. The sample amounted to 114 respondents. The sampling technique used in this study was purposive sampling. Data analysis was done univariate and bivariate. The results showed a relationship between parity (p value: 0.000) and anemia status (p value: 0.000) to the incidence of LBW. It is recommended for hospitals that preventive and promotive efforts can also be made in preventing low birth weight by providing counseling or counseling to pregnant women when pregnant women do antenatal care (ANC) checks during pregnancy.Keywords: Anemia, LBW, Parity.